IMPLEMENTATION OF "PEST-ENTOMOFAG" PROCEDURE IN BIOLOGICAL PROTECTION OF COTTON IN UZBEKISTAN - Kh.K, Yakhyaev; Kh.Z, Abdullaeva (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
The problem of development of optimum plans of biological fabrics work for release of useful entomophages (trichogramma, bracon, laxe wing) against the cotton pests (Heliothis armigera) for different zones with using the methods of modeling and programming has been examined. The period of owners development (Helio this armigera) and optimum periods of release of useful entomophages in dependence on weather conditions of the year were defined on the basis of algorithms working out.